HUBUNGAN STRES AKADEMIK DENGAN KEMATANGAN KARIR MAHASISWA TINGKAT AKHIR - Rusnawati Ellis; Ayu Novita Sari; Sumira Taip (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Final-year students face the dual pressure of completing academic requirements and preparing for the workforce, which can trigger academic stress and potentially hinder career development. This study aimed to examine the relationship between academic stress and career maturity among final-year university students. A quantitative correlational design was employed with 100 final-year students selected via purposive sampling. Data were collected using the Student-Life Stress Inventory (SLSI) by Gadzella and the Career Maturity Inventory (CMI) by Crites. Data analysis utilized descriptive statistics, Pearson product-moment correlation, and simple linear regression. The results revealed no significant relationship between academic stress and career maturity (p = 0.064 > 0.05). Descriptively, the majority of students experienced moderate academic stress (97%) but demonstrated high to very high career maturity (100%). This indicates that students can effectively compartmentalize academic pressures without compromising their vocational readiness and future career planning.